Physico Chemical Aspects of Pulliyankannu and Pulliyanthangal Lake Water in Ranipet Vellore District Tamilnadu India - B Senthil kumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Physico Chemical Aspects of Pulliyankannu and Pulliyanthangal Lake Water in Ranipet Vellore District Tamilnadu India